COMBINING AUDIO VISUAL WEB BLOG & QR CODE FOR LEARNING RECOUNT TEXT AT SENIOR HIGH SCHOOL 2 TRENGGALEK 2019/2020 ACADEMIC YEAR - Nurul Komsiah; Sri Utami Dewi (LinguA-LiterA: Journal of English Language Teaching Learning and Literature, 2020)
The objective of the research was to combining Audio Visual Web Blog and QR Code as a media in recount text.. The research design was educational research & development aimed at developing educational products. The second semester of eleventh grade XI MIPA 5 and XI MIPA 4 students in Senior High School 2 Trenggalek academic year 2019/2020. MIPA 5 as experimental group consist of 34 students and MIPA 4 as control group consist of 36 students. The instruments that was used in this research was questionnaire and test. The data collected by questionnaire and test analyzed quantitative. The product was developed in five steps based on students’ needs, recent theories related to the product, developing the educational product, evaluation from the expert who validates the product and field testing the product. The data was calculated by SPSS 25 and the result of sig. 2 tailed in t-test is 0.000 (<0.05), it means there was significant difference between experimental and control groups. From explanation above means that the product of this research, Audio Visual Web Blog, was an effective learning media to senior high school students to recount text material. Furthermore, it was suggested for people who find some benefit of this research.